Psychological contract and organizational misbehavior: Exploring the moderating and mediating effects of organizational health and psychological contract breach in Iraqi oil tanks company - Hadi Al-Abrrow; Alhamzah Alnoor; Eman Ismail; Bilal Eneizan; Hebah Zaki Makhamreh (Cogent Business & Management, 2019)
The study aimed to link psychological contract with organizational misbehavior directly and through the moderating and mediation effects of organizational health and psychological contract breach. For testing these relationships, the sample gathered from 224 employees, working in Iraqi Oil Tanks Company. The data collection tool was a structured questionnaire. The preliminary analysis was performed by using SPSS 22.0 while the hypothesis testing was done through AMOS, which measures structural equation modeling that helped in simultaneous testing of multiple relationships. The hypotheses of study underpinned by the social exchange theory and other related theoretical and empirical justifications found in the previous research results suggest a negative effect of PC on OM through the mediation of PCB. The findings were also consistent with prior studies concerning the interactive relationship between organizational health and psychological contract and their influence on organizational misbehavior. The theoretical and practical implications are also provided in this study, especially managers in Iraqi oil companies to be proactive in their role to minimize the impact of organizational misbehavior of employees through an open-door policy. Finally, this study helps managers to express their feedback, suggestions, and interaction with employees.
Keywords: 650; psychological contract; psychological contract breach; organisational health; organisational misbehaviour